Inventory of fishes in the upper Pelus River (Perak river basin, Perak, Malaysia) - Mohd Ikhwanuddin, Mat Esa; Amal, Mohammad Noor Azmai; Aziz, Azizul; Sepet, Johari; Talib, Abdullah; Ismail, Muhammad Faiz; Jamil, Nor Rohaizah (Pensoft Publishers, 2017)
The upper Pelus River is located in the remote area of the Kuala Kangsar district, Perak, Malaysia. Recently, the forest along the upper portion of the Pelus River has come under threat due to extensive lumbering and land clearing for plantations. Sampling at 3 localities in the upper Pelus River at 457, 156 and 89 m above mean sea level yielded 521 specimens representing 4 orders, 11 families, 23 genera and 26 species. The most abundant species was Neolissochilus hexagonolepis, followed by Homalopteroides tweediei and Glyptothorax major. The fish community structure indices was observed to increase from the upper to lower portion of the river, which might reflect differences in water velocity.